INCREASING STUDENTS’ READING INTEREST THROUGH READING CORNER (DULO ITO MO BACA) AT SDN 90 SIPATANA INDONESIA - Andre Saipi, Ananda Anastasya Akili, Winda Febriani Lapadang, Rina Umaya, Abdul Rahmat, Rusmin Husain (International Journal of Innovations in Engineering Research and Technology, 2022)
The purpose of this research is to increase students’ interest in reading, to introduce students to a variety of reading sources to be used as media, learning resources, and to provide an enjoyable reading experience. Based on observations made on October 10 2022, SDN 90 Sipatana had just been renovated so a reading corner had not been made yet because the principal of SDN 90 Sipatana had just moved and there were also several classes which did not yet have a reading corner because the school had just been renovated. After we found out that there was no reading corner in class V, so we decided to make our project, namely a literacy corner (reading corner). This study used qualitative research, in this study, data collection through observation, interviewing students using a questionnaire (instrument), then processing the data and making conclusions about how enthusiastic the fifth grade students at SDN 90 SIPATANA are in reading books. After conducting interviews and observations of the homeroom teacher for class V SDN 90 Sipatana, we then distributed questionnaires to students to find out the reading interests of class V students at SDN 90 Sipatana. Questionnaires were distributed to 28 students present, the questionnaire consisted of 10 questions that had to be filled in by students.